The influence mechanism of natural fractures on hydraulic fracture propagation in Mabei shale reservoir - Renzhong, Gan; Lianming, Fu; Dong, Ruan; Yue, Wu; Sicheng, Hu; Yi, Ding; Xiangjun, Liu (Frontiers in Earth Science, 2025)
The resource potential of shale in Fengcheng formation in Mabei is huge, but it must rely on efficient hydraulic fracturing technology to obtain reservoir stimulation and achieve economic development. The propagation of hydraulic fractures in shale oil reservoir is significantly affected by natural fractures, and the interaction mechanism between hydraulic fractures and natural fractures is the key of realizing the optimal fracturing design. In particular, shale oil reservoir has complex conditions, such as interlayer blocking effect, differentiation of natural fracture development and variation of formation dip angle. In that case, the influence law of natural fracture on hydraulic fracture propagation is not clear, which restricts efficient development of shale oil. Therefore, based on the mechanical properties of shale in the Fengcheng formation, numerical model of the intersection of natural fractures and hydraulic fracture has been built. This intersection behaviors with different approach angle, interlayer stress and strength, natural fracture development degree and formation inclination have been fully analyzed. The results indicate that the hydraulic fracture is more favorable to penetrate the natural fracture with the increasing of the approaching angle. The barrier layer is conducive to the hydraulic fracture penetrating the natural fracture, restricting activation of the natural fracture. Also, the stress barrier effect is greater than the strength barrier effect. With the increase of the development degree of natural fractures, a large number of fractures weaken the overall strength of the formation, which is more conducive to the propagation of hydraulic fractures. When formation dip is large and propagation from weak strength to strong strength formation, hydraulic fracture is more susceptible to the influence of natural fractures and show the characteristics of turning along natural fractures. Outcomes deepen the understanding of the interaction mechanism between natural fracture and hydraulic fracture, which is beneficial for the optimal fracturing design and providing theoretical support for shale oil exploitation.